Aggregation-induced emission material with high fluorescence quantum yield and large Stokes shift as well as preparation method and application of aggregation-induced emission material

By designing organic small molecule materials with ESIPT effect, the inefficiency problem caused by the self-absorption effect in fluorescent solar concentrators is solved, high fluorescence quantum efficiency and large Stokes displacement are achieved, and the photoelectric conversion efficiency is improved.

CN119528844AActive Publication Date: 2025-02-28THE CHINESE UNIV OF HONG KONG (SHENZHEN)

Patent Information

Application Number
CN202411617044.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Due to the self-absorption effect of the material, existing fluorescent solar concentrators lead to a reduced fluorescence intensity and low photoelectric conversion efficiency, and materials with large Stokes displacements usually have lower fluorescence quantum efficiency.

Method used

An organic small molecule material with an excited state intramolecular proton transfer (ESIPT) effect was designed, and its spectral characteristics were changed through group modification to synthesize aggregation-induced luminescent material with high fluorescence quantum efficiency and large Stokes displacement.

Benefits of technology

High fluorescence quantum efficiency and large Stokes displacement are achieved, completely eliminating the self-absorbing effect, improving the photoelectric conversion efficiency of fluorescent solar concentrators, and maintaining high stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses an aggregation-induced emission material with high fluorescence quantum yield and large Stokes shift as well as a preparation method and application of the aggregation-induced emission material, and belongs to the technical field of preparation of aggregation-induced emission materials. Comprising the following steps: carrying out Suzuki-Miyaura coupling reaction on organic boric acid and bromosalicylaldehyde to obtain an intermediate; and adding the intermediate, sodium pyrosulfite and aminothiophenol into an organic solvent, and then carrying out high-temperature reaction to prepare the aggregation-induced emission material. The aggregation-induced emission material is synthesized by a two-step method, so that the aggregation-induced emission material can be rapidly synthesized on a large scale, and the prepared aggregation-induced emission material also has the advantages of high fluorescence efficiency, large Stokes shift, good stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of aggregation-induced luminescence materials, and in particular relates to an aggregation-induced luminescence material with high fluorescence quantum yield and large Stokes shift, and a preparation method and application thereof. Background Art

[0002] Fluorescent solar concentrators can collect sunlight from a wide range, convert sunlight into high-quantum-efficiency fluorescence, and use the principle of total reflection to transmit fluorescence to optical devices at the edge of the device. Fluorescent solar concentrators achieve the collection of sunlight through three steps: absorbing light, reflecting fluorescence, and transmitting light. Solar cells installed at the edge of the fluorescent concentrator can effectively absorb high-intensity fluorescence, thereby improving the photoelectric conversion efficiency of solar cells per unit area. Common fluorescent groups now mainly include the following categories: organic small molecules, quantum dot materials, metal complexes, and perovskite materials. Among them, due to the phenomenon of spectral overlap between the absorption and emission of fluorescent materials themselves, it is also called self-absorption (reabsorption). Self-absorption will greatly reduce the fluorescence intensity reaching the edge of the device during the fluorescence transmission process, and at the same time weaken the photoelectric conversion efficiency of the fluorescent solar concentrator. The effect of self-absorption on fluorescent solar concentrators will be affected by the size of the material. Often, the larger the material area, the lower the efficiency. Not only that, the fluorescence quantum efficiency is also a major factor limiting the efficiency of fluorescent solar concentrators. Generally, materials with large Stokes shifts (low self-absorption effect) have lower fluorescence quantum efficiency.

[0003] Therefore, there is an urgent need to provide an aggregation-induced emission material having both high fluorescence quantum yield and large Stokes shift and a preparation method thereof. Summary of the invention

[0004] In order to overcome the defects or shortcomings of strong self-absorption and low efficiency of existing fluorescent solar concentrators, the present invention proposes an aggregation-induced luminescence material with high fluorescence quantum yield and large Stokes shift, and its preparation method and application. By designing an organic small molecule material with excited state intramolecular proton transfer (ESIPT) effect, that is, designing its spectrum, modifying groups at different chemical sites, thereby changing the absorption and emission spectrum, fluorescence quantum efficiency, Stokes shift, aggregate effect, etc., and then synthesizing it through a two-step method. It not only has the advantages of rapid and large-scale preparation, but also enables the prepared aggregation-induced luminescence material to have high fluorescence efficiency, large Stokes shift and good stability.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] An aggregation-induced emission material with large Stokes shift and high fluorescence quantum efficiency comprises the following structure:

[0008]

[0009] Beneficial effects: The present invention can make the aggregation-induced luminescence material have a large Stokes shift and high fluorescence quantum efficiency through molecular structure design and aggregation state structure adjustment, completely eliminate self-absorption, and thus prepare a fluorescent solar concentrator with both high efficiency and low loss.

[0010] The second technical solution of the present invention:

[0011] A method for preparing an aggregation-induced luminescence material with a large Stokes shift and high fluorescence quantum efficiency comprises the following steps:

[0012] The intermediate is obtained by Suzuki-Miyaura coupling reaction of organic boronic acid and bromosalicylaldehyde;

[0013] The intermediate, sodium pyrosulfite and aminothiophenol are added into an organic solvent, and then subjected to high temperature reaction to prepare the aggregation-induced luminescence material.

[0014] Preferably, the organic boronic acid includes any one of mesitylene boronic acid, mesitylene boronic acid, 9-anthracene boronic acid or acridin-9-yl boronic acid.

[0015] Preferably, the bromosalicylaldehyde is 3-bromosalicylaldehyde, 4-bromosalicylaldehyde or 5-bromosalicylaldehyde.

[0016] Preferably, the molar ratio of the organic boronic acid to brominated salicylaldehyde is (1.4-2):1; more preferably, the molar ratio of the organic boronic acid to brominated salicylaldehyde is 7:5;

[0017] The molar ratio of the intermediate, sodium pyrosulfite and aminothiophenol is 1:1:(1.2-2); more preferably, the molar ratio of the intermediate, sodium pyrosulfite and aminothiophenol is 5:5:6.

[0018] Preferably, the specific process of the Suzuki-Miyaura coupling reaction is:

[0019] Under the conditions of inert atmosphere, catalyst and alkali salt, the bromosalicylaldehyde, organic boronic acid and phosphorus ligand are mixed and heated to prepare the intermediate.

[0020] Further, the inert atmosphere is nitrogen; and / or

[0021] The catalyst is palladium acetate; and / or

[0022] The alkaline salt includes any one of anhydrous potassium phosphate, sodium tert-butoxide or potassium carbonate; and / or

[0023] The phosphorus ligand is any one of R-Phos (2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl), S-Phos (2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl) or X-Phos (2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl) ligands.

[0024] Furthermore, the heating process is: reacting at 105°C-110°C for 12-48h; more preferably, reacting at 105°C for 12h.

[0025] Furthermore, the heating process also includes cooling and purification processes.

[0026] Furthermore, the purification treatment is as follows: extracting the crude product obtained by cooling with a water and dichloromethane system, and then removing the solvent by reduced pressure distillation; and separating the obtained crude product by chromatography column using ethyl acetate and petroleum ether.

[0027] Preferably, the organic solvent is N,N-dimethylformamide.

[0028] Preferably, the conditions during the high temperature reaction are: reacting at 140° C. for 2-4 hours.

[0029] The third technical solution of the present invention:

[0030] The aggregation-induced luminescence material with large Stokes shift and high fluorescence quantum efficiency is used in the field of preparing fluorescent solar concentrators.

[0031] The fourth technical solution of the present invention:

[0032] A fluorescent solar concentrator is prepared from the above-mentioned aggregation-induced luminescence material.

[0033] Preferably, the fluorescent solar concentrator, in addition to the base layer, also includes a light waveguide layer containing the aggregation-induced emission material.

[0034] The fifth technical solution of the present invention:

[0035] The method for preparing the fluorescent solar concentrator comprises the following steps:

[0036] subjecting the aggregation-induced emission material and the mixed solvent to ultrasonic treatment in sequence to obtain a mixed solution;

[0037] The mixed solution is scraped onto the surface of the base layer, and then subjected to a heating treatment to obtain the fluorescent solar concentrator.

[0038] Preferably, the mixed solvent consists of polymethyl methacrylate and toluene, wherein the concentration of polymethyl methacrylate is 18-22%.

[0039] Preferably, the duration of the ultrasonic process is 20 min.

[0040] Preferably, in the mixed solution, the concentration of the aggregation-induced emission material is 2.1%-6.3%.

[0041] Preferably, the conditions during the heating treatment are: performing solvent volatilization to form a film in an oven at 80° C., and the volatilization time is 48 hours.

[0042] Compared with the prior art, the present invention has the following advantages and technical effects:

[0043] The present invention designs and synthesizes an aggregation-induced luminescence material with an excited state intramolecular proton transfer (ESIPT) effect, wherein the quantum yield and Stokes shift of organic small molecules in the aggregated state are significantly improved by adjusting the aggregated state structure, and can be close to 200nm.

[0044] The present invention combines an aggregation-induced luminescence material with high quantum yield and large Stokes shift on a glass surface by coating technology to form an optical waveguide layer, thereby preparing a fluorescent solar concentrator. By testing the photoelectric conversion efficiency of fluorescent solar concentrators of different sizes, it is proved that the efficiency decays slightly when the size increases, and the efficiency is still maintained at 0.41% when the size is 400 square centimeters (photoelectric conversion efficiency = solar cell power / sunlight power). BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0046] Figure 1 This is a real picture of the fluorescent solar concentrator prepared in Example 5 under sunlight;

[0047] Figure 2 This is a graph of the fluorescence quantum yields of compounds C1, C2, and C3 prepared in Example 2;

[0048] Figure 3 The current density-voltage characteristic curve (JV characteristic curve) of the fluorescent solar concentrators of different sizes prepared in Example 5 under sunlight;

[0049] Figure 4 The chemical synthesis route for preparing A1, A2 and A3 in Example 1 of the present invention is as follows;

[0050] Figure 5 ] are the absorption and emission spectra of compound C1 prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0051] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0052] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0053] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0054] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0055] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0056] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0057] The raw materials used in the present invention are all purchased from the market.

[0058] The technical solution of the present invention is further illustrated by the following embodiments.

[0059] Example 1

[0060] like Figure 4As shown, a method for preparing an aggregation-induced emission material with a large Stokes shift and high fluorescence quantum efficiency comprises the following steps:

[0061] 1. Preparation of A1a, A2a, A3a:

[0062] In N 2 In an atmosphere, 3-bromosalicylaldehyde (10mmol) was added to a 250mL three-necked flask, and then trimethylphenylboronic acid (14mmol) and anhydrous potassium phosphate (60mmol) were added to the three-necked flask, and 90mL toluene and 15mL water were added to the system respectively and deoxygenated, and finally palladium acetate catalyst (0.50mmol) and R-Phos (1mmol) ligand were added. The reaction mixture was reacted at 105°C for 12h, and the reaction progress was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature, and the crude product was extracted with water and dichloromethane system, and then the solvent was distilled off under reduced pressure. The crude product was separated by chromatography using ethyl acetate and petroleum ether (the volume ratio of the two was 2:98), thereby obtaining a colorless oily product A1a;

[0063] Among them, A1a (yield 98%), 1 HNMR (500MHz, CDCl 3 )δ11.21(s,1H),9.98(s,1H),7.48(s,1H),7.48-7.39(m,1H),7.19(d,J=8.4Hz,1H),7.12(s,2H),2.48(s,3H),2.20(s,6H);

[0064] The preparation process of A2a is the same as that of A1a, except that 3-bromosalicylaldehyde is replaced by 4-bromosalicylaldehyde. A2a (yield 95%), 1 H NMR (500 MHz, CDCl 3 )δ11.32-11.26(m,1H),10.03-9.97(m,1H),7.70(td,J=7.8,4.7Hz,1H),7 .07-7.03(m,2H),6.97-6.90(m,2H),2.52-2.38(m,3H),2.18-2.12(m,6H);

[0065] The preparation process of A3a is the same as that of A1a, except that 3-bromosalicylaldehyde is replaced by 5-bromosalicylaldehyde. A3a (yield 97%), 1 H NMR (500 MHz, CDCl 3)δ11.28(t,J=2.9Hz,1H),10.04-9.97(m,1H),7.54-7.50(m,1H),7.50-7.44(m,1H),7 .23(dd,J=7.4,4.5Hz,1H),7.16(s,2H),2.53(d,J=4.0Hz,3H),2.25(t,J=3.3Hz,6H).

[0066] 2. Preparation process of compounds A1, A2, A3:

[0067] A colorless oily product A1a (5 mmol), sodium metabisulfite (5 mmol) and aminothiophenol (6 mmol) were added to 20 mL of N,N-dimethylformamide. The reaction mixture was reacted at 140°C for 4 hours, and the reaction progress was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature and a large amount of water was added to produce a large amount of crude product. The crude product was washed with a large amount of methanol to obtain a white powder product A1 (yield 92%). 1 H NMR;

[0068] The preparation process of A2 is the same as the preparation process of A1, except that A1a is replaced by A2a. A2 (yield 90%), 1 H NMR;

[0069] The preparation process of A3 is the same as the preparation process of A1, except that A1a is replaced by A3a. A3 (yield 95%), 1 H NMR.

[0070] Example 2

[0071] A method for preparing an aggregation-induced luminescence material with a large Stokes shift and high fluorescence quantum efficiency comprises the following steps:

[0072] 1. Preparation of C1a, C2a, and C3a

[0073] In N 2In an atmosphere, 3-bromosalicylaldehyde (10mmol), 9-anthraceneboronic acid (14mmol) and anhydrous potassium phosphate (60mmol) were added to a 250mL three-necked flask, and 90mL toluene and 15mL water were added to the system for deoxygenation, and finally palladium acetate catalyst (0.50mmol) and R-Phos (1mmol) ligand were added. The reaction mixture was reacted at 105°C for 12h, and the reaction progress was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature, and the crude product was extracted with water and dichloromethane system, and then the solvent was distilled off under reduced pressure. The crude product was separated by chromatography using ethyl acetate and petroleum ether (the volume ratio of the two was 2:98), thereby obtaining a white crystalline product C1a (yield 94%), 1 H NMR (500 MHz, CDCl 3 )δ11.18(s,1H),10.08(s,1H),8.55(s,1H),8.07(d,J=8.5Hz,2H),7.80(dd,J=7.8,1.8Hz,1H),7.60-7 .57(m,3H),7.47(ddd,J=8.1,6.5,1.1Hz,2H),7.38(ddd,J=8.1,6.5,1.3Hz,2H),7.28(d,J=7.5Hz,1H);

[0074] The preparation process of C2a is the same as that of C1a, except that 3-bromosalicylaldehyde is replaced by 4-bromosalicylaldehyde. The prepared pale yellow crystalline powder C2a (yield 98%) is 1 H NMR (500 MHz, CDCl 3 )δ11.23(s,1H),10.07(s,1H),8.54(s,1H),8.06(d,J=8.5Hz,2H),7.77(d,J=7.6Hz,1H),7.63(dd,J=8 .9,1.2Hz,2H),7.48(ddd,J=8.4,6.6,1.1Hz,2H),7.39(ddd,J=8.9,6.4,1.3Hz,2H),7.14-7.09(m,2H);

[0075] The preparation process of C3a is the same as that of C1a, except that 3-bromosalicylaldehyde is replaced by 5-bromosalicylaldehyde. The white crystalline product C3a (yield 95%) is obtained. 1 H NMR (500 MHz, CDCl 3)δ11.19(s,1H),9.95(s,1H),8.54(s,1H),8.07(d,J=8.5Hz,2H),7.65(dd,J=9.1,1.5Hz,3H),7.61(dd,J=8 .4, 2.2Hz, 1H), 7.49 (ddd, J=8.3, 6.6, 1.1Hz, 2H), 7.39 (ddd, J=8.8, 6.5, 1.3Hz, 2H), 7.24 (d, J=8.4Hz, 1H).

[0076] 2. Preparation process of compounds C1, C2, C3:

[0077] C1a (5 mmol), sodium metabisulfite (5 mmol) and aminothiophenol (6 mmol) were added to 20 mL of N,N-dimethylformamide. The reaction mixture was reacted at 140°C for 4 h, and the reaction progress was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature and a large amount of water was added to produce a large amount of crude product. The crude product was washed with a large amount of methanol to obtain a white powder product C1 (yield 97%). 1 H NMR (500 MHz, CDCl 3 )δ8.56(s,1H),8.09(d,J=8.5Hz,2H),7.98-7.91(m,2H),7.81(d,J=8.0Hz,1H),7.74(d,J=8.8Hz,2H),7.51-7.35(m,7H),7.21(t,J=7.6Hz,1H);

[0078] The preparation process of C2 is the same as the preparation process of C1, except that C1a is replaced by C2a. The prepared C2 (yield 94%), 1 H NMR (500 MHz, CDCl 3 )δ8.56(s,1H),8.10(d,J=8.3Hz,3H),8.01(d,J=7.9Hz,1H),7.94(d,J=7.9Hz,1H),7.82(d,J=8.8Hz,2H),7.63-7. 56(m,1H),7.55-7.47(m,3H),7.43(ddd,J=8.9,6.4,1.3Hz,2H),7.29(d,J=8.8Hz,2H),7.09(dd,J=7.9,1.6Hz,1H;

[0079] The preparation process of C3 is the same as that of C1, except that C1a is replaced by C3a. The prepared C3 (yield 92%), 1 HNMR (500MHz, CDCl 3)δ8.54(s,1H),8.07(dd,J=12.7,8.4Hz,3H),7.85(d,J=7.9Hz,1H),7.83- 7.72(m,3H),7.55-7.46(m,4H),7.43-7.37(m,3H),7.35(d,J=8.3Hz,1H).

[0080] Example 3

[0081] In N 2 In the atmosphere, 3-bromosalicylaldehyde (10mmol), triisopropylphenylboronic acid (14mmol) and anhydrous potassium phosphate (60mmol) were added to a 250mL three-necked flask, and 90mL toluene and 15mL water were added to the system for deoxygenation, and finally palladium acetate catalyst (0.50mmol) and R-Phos (1mmol) ligand were added. The reaction mixture was reacted at 110℃ for 12h, and the reaction process was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature, and the crude product was extracted with water and dichloromethane system, and then the solvent was removed by reduced pressure distillation. The crude product was separated by chromatography column using ethyl acetate and petroleum ether (the volume ratio of the two was 2:98), thereby obtaining a white intermediate product (yield 84%). The white intermediate product (5mmol), sodium pyrosulfite (5mmol) and aminothiophenol (6mmol) were added to 20mL N,N-dimethylformamide. The reaction mixture was reacted at 140°C for 4 hours, and the reaction progress was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature, and a large amount of water was added to produce a large amount of crude product. The obtained crude product was washed with a large amount of methanol to obtain a white powder product B1 (yield 97%);

[0082] The preparation process of B2 is the same as the preparation process of B1, except that 3-bromosalicylaldehyde is replaced by 4-bromosalicylaldehyde. The prepared B2 (yield 92%);

[0083] The preparation process of B3 is the same as the preparation process of B1, except that 3-bromosalicylaldehyde is replaced by 5-bromosalicylaldehyde. The prepared B3 (yield 93%).

[0084] Example 4

[0085] In N 2In the atmosphere, 3-bromosalicylaldehyde (10mmol), acridin-9-ylboronic acid (14mmol) and anhydrous potassium phosphate (60mmol) were added to a 250mL three-necked flask, and 90mL toluene and 15mL water were added to the system for deoxygenation, and finally palladium acetate catalyst (0.50mmol) and R-Phos (1mmol) ligand were added. The reaction mixture was reacted at 110℃ for 12h, and the reaction process was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature, and the crude product was extracted with water and dichloromethane system, and then the solvent was distilled off under reduced pressure. The crude product was separated by chromatography using ethyl acetate and petroleum ether (the volume ratio of the two was 5:95), thereby obtaining a white intermediate product (yield 75%). The light yellow intermediate product (5mmol), sodium pyrosulfite (5mmol) and aminothiophenol (6mmol) were added to 20mL N,N-dimethylformamide. The reaction mixture was reacted at 140°C for 4 hours, and the reaction progress was tracked by TLC plate. After the reaction was completed, the reaction solution was cooled to room temperature, and a large amount of water was added to produce a large amount of crude product. The crude product was washed with a large amount of methanol to obtain a light yellow powder product D1 (yield 90%);

[0086] The preparation process of D2 is the same as the preparation process of D1, except that 3-bromosalicylaldehyde is replaced by 4-bromosalicylaldehyde. The prepared D2 (yield 92%);

[0087] The preparation process of D3 is the same as the preparation process of D1, except that 3-bromosalicylaldehyde is replaced by 5-bromosalicylaldehyde. D3 (yield 88%) is obtained.

[0088] Example 5: Preparation process of a fluorescent solar concentrator:

[0089] Dissolve 5g of polymethyl methacrylate in a certain amount of toluene, stir to completely dissolve it and prepare a solution with a specific gravity of 18-22% (mass percentage of polymethyl methacrylate). Take a certain amount of the C1 compound prepared in Example 2, mix the two evenly, and completely remove the bubbles by ultrasonication for 20 minutes to prepare a solution with a concentration of 6.3% (mass percentage of the C1 compound). Apply the obtained solution on the surface of the glass substrate using a coating machine, put it in an oven at 80°C for solvent evaporation to form a film, and the evaporation time is 48 hours to obtain an aggregation-induced luminescence material with high fluorescence quantum yield and low loss to prepare a fluorescent solar concentrator (film thickness is 20μm).

[0090] Example 6: Preparation process of a fluorescent solar concentrator:

[0091] The difference from Example 5 is that the solution is prepared with a C1 compound concentration of 4.2% by weight. The other steps and conditions are the same as those in Example 5.

[0092] Example 7: Preparation process of a fluorescent solar concentrator:

[0093] The difference from Example 5 is that the solution is prepared with a concentration of 2.1% by weight of the C1 compound. The other steps and conditions are the same as those of Example 5.

[0094] Example 8: Preparation process of a fluorescent solar concentrator:

[0095] The difference from Example 5 is that the C1 compound is replaced by the C3 compound. The other steps and conditions are the same as those of Example 5.

[0096] Example 9: Preparation process of a fluorescent solar concentrator:

[0097] The difference from Example 6 is that the C1 compound is replaced by the C3 compound. The other steps and conditions are the same as those of Example 6.

[0098] Example 10: Preparation process of a fluorescent solar concentrator:

[0099] The difference from Example 7 is that the C1 compound is replaced by the C3 compound. The other steps and conditions are the same as those of Example 7.

[0100] Figure 1 This is a real picture of the fluorescent solar concentrator prepared in Example 5 of the present invention under sunlight. Figure 1 It can be seen that it has the advantages of being colorless and highly transparent, and that the glass edge produces strong fluorescence.

[0101] Figure 2 The fluorescence quantum yield diagram of the compounds C1, C2, and C3 prepared in Example 2 of the present invention shows that the three compounds all produce an obvious fluorescence quantum yield increase effect in the aggregated state (film state and crystal state), proving that they have an aggregation-induced emission effect and can provide high efficiency for fluorescent solar concentrators. The film state refers to the compound being doped with 2.1% (mass percentage of the compound) in a 100 mg / mL tetrahydrofuran solution of polymethyl methacrylate and spin-coated into a film; the crystal state refers to the compound being obtained by solvent evaporation in a saturated chloroform solution.

[0102] Figure 3 The current density-voltage characteristic curve (JV characteristic curve) of the fluorescent solar concentrator prepared in Example 5 of the present invention under sunlight is shown in FIG. Figure 3 It can be seen that the photoelectric conversion efficiency does not decay significantly with the increase of size, which proves that the efficiency decays slightly when the size increases.

[0103] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An aggregation-induced emission material with large Stokes shift and high fluorescence quantum efficiency, characterized in that: Its general structural formula is: In the above formula, R1, R2 and R3 are selected from H, Any of; Among them, only one of R1, R2 and R3 is not H.

2. A method for preparing an aggregation-induced emission material having a large Stokes shift and high fluorescence quantum efficiency, characterized in that: The following steps are involved: The intermediate is obtained by Suzuki-Miyaura coupling reaction of organic boronic acid and bromosalicylaldehyde; The intermediate, sodium pyrosulfite and aminothiophenol are added into an organic solvent, and then reacted at high temperature to prepare the aggregation-induced emission material according to claim 1.

3. The method for preparing an aggregation-induced emission material having a large Stokes shift and high fluorescence quantum efficiency according to claim 2, characterized in that: The organic boronic acid includes any one of mesitylene boronic acid, mesitylene boronic acid, 9-anthracene boronic acid or acridin-9-yl boronic acid; and / or The bromosalicylaldehyde is 3-bromosalicylaldehyde, 4-bromosalicylaldehyde or 5-bromosalicylaldehyde.

4. The method for preparing an aggregation-induced emission material having a large Stokes shift and high fluorescence quantum efficiency according to claim 2, characterized in that: The molar ratio of the organic boronic acid to the brominated salicylaldehyde is (1.4-2):

1. The molar ratio of the intermediate, sodium pyrosulfite and aminothiophenol is 1:1:(1.2-2).

5. The method for preparing an aggregation-induced emission material having a large Stokes shift and high fluorescence quantum efficiency according to claim 2, characterized in that: The specific process of the Suzuki-Miyaura coupling reaction is: Under the conditions of inert atmosphere, catalyst and alkali salt, the bromosalicylaldehyde, organic boronic acid and phosphorus ligand are mixed and heated to prepare the intermediate.

6. The method for preparing an aggregation-induced emission material having a large Stokes shift and high fluorescence quantum efficiency according to claim 5, characterized in that: The heating process is: reacting at 105° C.-110° C. for 12-48 hours.

7. The method for preparing an aggregation-induced emission material having a large Stokes shift and high fluorescence quantum efficiency according to claim 2, characterized in that: The conditions in the high temperature reaction process are: reacting at 140° C. for 2-4 hours.

8. Use of the aggregation-induced emission material with large Stokes shift and high fluorescence quantum efficiency as claimed in claim 1 in the field of preparing fluorescent solar concentrators.

9. A fluorescent solar concentrator, comprising a substrate, characterized in that: It also includes an optical waveguide layer containing the aggregation-induced emission material according to claim 1.

10. A method for preparing a fluorescent solar concentrator, characterized in that: The following steps are involved: The aggregation-induced emission material and the mixed solvent are mixed, and then subjected to ultrasonic treatment to obtain a mixed solution; The mixed solution is scraped onto the surface of a base layer, and then subjected to a heating treatment to obtain the fluorescent solar concentrator as claimed in claim 9.

Citation Information

Patent Citations

  • 2-(2'-hydroxyphenyl) benzoxazole compound containing substituent at 4-site and preparation method and application thereof

    CN106749094A

  • PH (potential of hydrogen) fluorescence probe on basis of 2-(2'-hydroxycyclohexyl phenyl ketone) benzothiazole derivatives, method for preparing pH fluorescence probe and application thereof

    CN106810511A

  • Photoactivated aggregation-inducing luminescent probe having in-situ generation capability and preparation and application thereof

    CN108409685A

  • Ratiometric fluorescent probe for detecting pH in cells as well as preparation method and application of ratiometric fluorescent probe.

    CN109761931A

  • Organic light-emitting diode and preparation method and application thereof

    CN115101699A

Cited By

  • Multifunctional luminescent molecule with excited-state intramolecular proton transfer and aggregation-induced fluorescence emission effects and preparation method thereof

    CN121627676A

  • A multifunctional luminescent molecule exhibiting intramolecular proton transfer and aggregation-induced fluorescence emission in excited-state molecules and its preparation method thereof.

    CN121627676B